Panel data regression analysis utilizing CEM and FEM methods in relation to the profitability of Sharia commercial banks (2015 – 2024) - Mahfudhotin; Sari, Kiky Novita (Journal Focus Action of Research Mathematic (Factor M), 2025)
Panel data regression analysis is typically utilized to investigate individuals or entities over different time spans. In this research, the regression models applied to the panel data include the Common Effect Model (CEM) and the Fixed Effect Model (FEM). To evaluate which model is superior to the other, the Chow test estimation method was utilized. This evaluation focused on the Return on Assets profitability data from nine Islamic Commercial Banks during the timeframe from 2015 to 2024. The findings from the Chow test analysis indicated that the Common Effect Model was the most suitable, with Non-Performing Financing identified as a significant factor influencing profitability (Return on Assets) in the Islamic Commercial Banks registered with the Financial Services Authority.